The Septuagint Text of Ezra 9.2 - Louy, Stephen D. (The Bible translator, 2014)
In the book of Ezra, the scribe is depicted as lamenting the news that the “holy seed” of Israel has “mixed itself with the peoples of the lands” through marriage. Such a mixing with outsiders is, apparently, to be avoided. But by the time of the LXX translation, Ezra laments that the “holy seed” has “disappeared into the peoples of the land.” This study explores the possible reasons for this change between the Hebrew and Greek texts, and proposes that an intentional change by the Greek translator is likely in order to address the cultural situation of his audience.